Planar rectilinear drawings of outerplanar graphs in linear time - Frati, Fabrizio (Computational geometry : theory and applications, 2022)
We show how to test in linear time whether an outerplanar graph admits a planar rectilinear drawing, both if the graph has a prescribed plane embedding that the drawing has to respect and if it does not. Our algorithm returns a planar rectilinear drawing if the graph admits one.